Do labour market institutions matter? Micro-level wage effects of international outsourcing in three European countries - Ingo Geishecker; Holger Görg; Jakob Roland Munch (Institute for the Study of Labor (IZA), 2007)
This paper studies the impact of outsourcing on individual wages in three European countries with markedly different labour market institutions: Germany, the UK and Denmark. To do so we use individual level data sets for the three countries and construct comparable measures of outsourcing at the industry level, distinguishing outsourcing by broad region. Estimating the same specification on different data show that there are some interesting differences in the effect of outsourcing across countries. We discuss some possible reasons for these differences based on labour market institutions. – International outsourcing ; individual wages ; labour market institutions
Keywords: F16; 330; Arbeitsmarkt; Institutionelle Infrastruktur; Outsourcing; Offshoring; Auslandsproduktion; Lohn; Vergleich; Dänemark; Deutschland; Großbritannien